The Effect of Liquidity, Leverage and Bank's Size on Bank's Profitability of Indonesian Listed Bank - Lestari, Henny Setyo (Jurnal Manajemen, 2021)
The purpose of this study is to determine the impact of liquidity, leverage and bank size on profitability in Indonesian conventional banking sector as the influencer of economic movements in this country. This study employed the total of 29 commercial banks listed on Indonesia Stock Exchange during the period of 2010-2019. There are total of 290 observations made in the study. The dependent variable used in this study is bank's profitability measured by return on asset (ROA), return on equity (ROE) and net interest margin (NIM). The independent variables are liquidity measured by loan to deposit ratio (LDTR), leverage measured by equity to asset ratio (ETAR) and bank size measured by natural log of total asset (LNTA) . The result shows that liquidity was observed to has insignificant negative impact on bank's ROA and ROE, and positively affect NIM but statistically insignificant. While leverage has negative but insignificant impact on ROA and NIM, and significanlly has negative affect on ROE. Meanwhile, bank size has positive and significant impact on ROA, then has insignificant negative impact on ROE, and significantly has negative affect on NIM.This study could help the internal management of Indonesian conventional banking sector to make policy and decision in order to improve bank's profitability.